If the function  $f(x) =  - 4{e^{\left( {\frac{{1 - x}}{2}} \right)}} + 1 + x + \frac{{{x^2}}}{2} + \frac{{{x^3}}}{3}$ and $g(x)=f^{-1}(x) \,;$ then the value of $g'(-\frac{7}{6})$ equals

  • A

    $\frac{1}{5}$

  • B

    $- \frac{1}{5}$

  • C

    $\frac{6}{7}$

  • D

    $ -\frac{6}{7}$

Similar Questions

In which of the following functions is Rolle's theorem applicable ?

If for $f(x) = 2x - {x^2}$, Lagrange’s theorem satisfies in $[0, 1]$, then the value of $c \in [0,\,1]$ is

Which of the following function can satisfy Rolle's theorem ?

Rolle's theorem is not applicable to the function $f(x) = |x|$ defined on $ [-1, 1] $ because

From mean value theorem $f(b) - f(a) = $ $(b - a)f'({x_1});$   $a < {x_1} < b$ if $f(x) = {1 \over x}$, then ${x_1} = $